The Urgency for Enactment of Digital Wallet Regulation (Study Case on South Korea Regulation) - Kurniawan Sutrisno Hadi (Universitas Negeri Semarang in collaboration with Ikatan Penulis Mahasiswa Hukum Indonesia, 2023)
In the digital era, the payment system has experienced transformations. Currently, transferring money or payment can be conducted through online and online methods. A digital wallet offers a financial service through online methods. However, there is no designated law or act that regulates digital wallet services in Indonesia. Indonesia has regulated digital wallet services under the Bank Indonesian Regulation (central bank) and Financial Services Authority (OJK) Regulation. This study aims to examine and analyze the urgency for enacting digital wallet regulation in Indonesia and provide a precise regulation about digital wallets from South Korean regulations. This type of research is normative research using a statutory approach to examine the urgency of enacting digital wallet regulation in Indonesia and using a comparative approach to provide a precise regulation about digital wallets from the study of South Korean regulations. The results of this study indicate that regulation at the law or act level concerning digital wallets is needed. There are several elements that must be governed in the digital wallet regulation, such as general provision; consumer protection; registration and license; supervision; obligations and prohibitions; and penalty provisions.